Development of Electronic Pocket Book “ Business Tips Bettas Fish millionaire By Using OMNI Channel Marketing Strategy” - Koprasert, Kanokpatch; Patthirasinsiri, Natpasuth; Ngamyingyong, Nittaya; Kongka, Jirawat (Journal of Vongchavalitkul university, 2020)
The research study aims to 1) develop an electronic pocket book titled "Business Tips. Siamese fighting fish using multi-channel marketing strategies." 2) The measurement efficiency of electronic pocket books, titled "Business Tips. Siamese fighting fish using multi-channel marketing strategies. “The research tool is structured interview. The Information group is a group of content experts provides of three people and 3 expert persons in technology and digital media. The sample was selected using purposive sampling. Questionnaires and the general public to determine the sample size by using a formula of 400 Roscoe, method convenience sampling. The results showed that the creation of an electronic pocket book “Business Tips Bettas Fish millionaire Using a variety of marketing channel strategies" using Canva development of multimedia e-book format. Photos (Image), narration (Sound), animation, 2D, 3D, VHS (Video) the content consists of 9 sections detail involves a startup Business of fish sales through online and offline. Strategies for fish fighting sales a variety of channels (OMNI Channel).By measuring the performance of electronic pocket books with featured elements: performance and effectiveness, the assessment is very good ( = 4.51) and integrity, Customer Learning Satisfaction and Coverage Results Assessment are at a good level ( = 4.47, 4.47, 4.40 and 4.36).